2018
DOI: 10.13189/ujp.2018.060101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Networking on the Divorce Process

Abstract: This study aims to examine the opinions of people who have divorced because of their spouses' relationships on social network, and who stated that they were deceived by their spouses on internet. In the study, case study method was used since the study deals with "the people who have divorced for their spouses deceived them on the internet". The study was carried out with ten participants (five of them are male and five of them are female) living in Trabzon, Turkey and divorced in 2013 for they were deceived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Although the use of online sexual content can create positive experiences for some individuals (Bridges & Morokoff, 2011), Eichenberg et al (2017) and Aydın et al (2018) showed that users with online sexual activities in the cyberspace were reluctant to have real sexual relationships. Because sexual dysfunction can be due to disturbances in tendency, arousal, orgasm, and sexual pain (APA, 2013), the loss of sexual desire can be associated with female sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of online sexual content can create positive experiences for some individuals (Bridges & Morokoff, 2011), Eichenberg et al (2017) and Aydın et al (2018) showed that users with online sexual activities in the cyberspace were reluctant to have real sexual relationships. Because sexual dysfunction can be due to disturbances in tendency, arousal, orgasm, and sexual pain (APA, 2013), the loss of sexual desire can be associated with female sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that cybersex or pornography as an expression of internet addiction can be a contributing factor to couples' separation and divorce [43]. In addition, cybersex users who have uncontrolled use of the internet for sexual activities have reported sexual aversion and dissatisfaction with their spouses [42] and a decline in their desire for sexual intercourse [44,45]. While appropriate sexual activity is the benchmark of physical and mental health in a healthy marriage [46], couple burnout may result from the lack of sexual relationship.…”
Section: Theoretical Hypothesismentioning
confidence: 99%
“…A study conducted among Turkish divorced users showed that spending a lot of time on SNS reduces the quality of communication between partners. The use of SNS also reduces love and interest, and leads to behavioral changes such as being irresponsibility, which in turn may lead to violence such as slapping, throwing objects, and pushing (Aydin et al, 2018).…”
Section: Studies Also Indicated Escalating Deterioration Of Marital Relationships the Use Of Sns Causes A Lack Of Love Interest And Intermentioning
confidence: 99%
“…On the extreme, some studies proved that the misusage of SNS is one of the reasons that lead to divorce. A study conducted on Turkish divorced users concluded that using SNS by one of the spouses for secret virtual relationships with the other sex leads to negative effects on family, which play a great role in divorce (Aydin et al, 2018). Some respondents of married and single users in Tunisia (36%) showed that using SNS between spouses leads to divorce (Al-Fakeh, 2018).…”
Section: Another Social Effect Of Intense Usage Of Sns Is Marital Infidelitymentioning
confidence: 99%